Variability of peripheral pulse wave velocity in patients with diabetes mellitus type 2 during orthostatic challenge - Svačinová, J; Hrušková, J; Jakubík, J; Budinskaya, K; Hidegová, S; Fabšík, M; Sieglová, H; Kaščáková, Z; Novák, J; Nováková, Z (Physiological research, 2020)
Diabetes mellitus 2 (DM2) is the seventh cause of death worldwide. One of the reasons is late diagnosis of vascular damage. Pulse wave velocity (PWV) has become an independent marker of arterial stiffness and cardiovascular risk. Moreover, the previous studies have shown the importance of beat-to-beat PWV measurement due to its variability among the heart cycle. However, variability of PWV (PWVv) of the whole body hasn't been examined yet. We have studied a group of DM II and heathy volunteers, to investigate the beat-to-beat mean PWV (PWVm) and PWVv in the different body positions. PWV of left lower and upper extremities were measured in DM2 (7 m/8 f, age 68+/-10 years, BP 158/90+/-19/9 mm Hg) and healthy controls (5 m/6 f, age 23+/-2 years, BP 117/76+/-9/5 mm Hg). Volunteers were lying in the resting position and of head-up-tilt in 45° (HUT) for 6 min. PWVv was evaluated as a mean power spectrum in the frequency bands LF and HF (0.04-0.15 Hz, 0.15-0.5 Hz). Resting PWVm of upper extremity was higher in DM2. HUT increased lower extremity PWVm only in DM2. Extremities PWVm ratio was significantly lower in DM2 during HUT compared to controls. LF and HF PWVv had the same response to HUT. Resting PWVv was higher in DM2. Lower extremity PWVv increased during HUT in both groups. PWVm and PWVv in DM2 differed between extremities and were significantly influenced by postural changes due to hydrostatic pressure. Increased resting PWVm and PWVv in DM2 is a marker of increased arterial stiffness.
Keywords: dospělí; Female; Pulse Wave Analysis; Adult; mladý dospělý; ženské pohlaví; Diabetes Mellitus, Type 2; lidé; postura těla; analýza pulzové vlny; tuhost cévní stěny; Vascular Diseases; diabetes mellitus 2. typu; studie případů a kontrol; rychlost toku krve; Blood Flow Velocity; srdeční frekvence; nemoci cév; Male; Case-Control Studies; Aged; Posture; Young Adult; senioři; mužské pohlaví; Vascular Stiffness; Heart Rate; Humans